Implementation of IOT on Laboratory Door Security System Using - Dian Noviandri; Rizaldy Khair (Sean Institute, 2022)
The door security system using RFID is one of the many systems that can be used to increase the level of security on the doors of houses, classrooms, warehouses and so on. The door security system uses RFID as a medium to read or identify so that the door can open. It uses a relay as a link and breaker of electric current that is flowed to the load (Solenoid Door Lock). It uses LCD as a notification whether RFID successfully identifies what not. When RFID identifies the card and the condition of the card that the RFID reads successfully then the LCD will pop up the text